The analysis of the cartographic materials for the creation of GIS of Antarctic station «Academician Vernadsky» - Litvinov, V.; Glotov, V.; Kolb, I.; Chyzevsky, V. (Ukrainian Antarctic Journal, 2006)
In the article the existing topographic materials are analyzed for the region of Antarctic station «Academician Vernadsky». The main purpose is their usage for the creation of GIS. Large-scale topographic plans which are created for the territory where the main scientific investigations are held will have the highest priority. This is because on such cartographic materials we can more precisely determine the coordinates of the points of interest and create projects for such research works. The projects of the next cartographic works in the region of station «Academician Vernadsky» are given.